Lingual mucosal graft urethroplasty 12 years later: Systematic review and meta-analysis - Alberto Abrate; Andrea Gregori; Alchiede Simonato (Asian Journal of Urology)
Objective: To evaluate the functional results and complications of the lingual mucosal graft (LMG) urethroplasty and to sum up the current state of the art of this surgical technique. Methods: A systematic search of PubMed and Scopus electronic databases was performed, according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Studies involving male patients treated with LMG urethroplasty for urethral stricture were included. Complete protocol is available at http://www.crd.york.ac.uk/PROSPERO/display_record.php?ID=CRD42017080121. A meta-analysis comparing functional and long-term oral complication outcomes of LMG and buccal mucosal graft (BMG) was performed, calculating the odds ratio (OR) and 95% confidence interval (CI). Results: Twenty original articles were included in the qualitative analysis. Strictures of 1.5–16.5 cm have been treated with LMG urethroplasty, due to the improvement of harvesting technique and very low rate of long-term oral complications. Very good functional results have been reported by different authors for LMG urethroplasty, with lower rate of oral complications than BMG. The meta-analysis included six comparative studies involving 187 and 178 patients treated with LMG and BMG urethroplasty, respectively. An OR of 1.65 (95% CI [0.95–2.87], I2 = 0%) and 0.18 (95% CI [0.03–1.26], I2 = 68%) were found for LMG vs. BMG urethroplasty, in terms of success and oral complication rate, respectively. Conclusion: LMG urethroplasty can be reasonably considered a first choice technique for urethral stricture with very good results. Oral complications are temporary and minimally disabling, basically less than those for BMG, and depend mainly on the graft extent. Keywords: Lingual mucosal graft, Meta-analysis, Systematic review, Urethral stricture, Urethroplasty